Churches in the mirror: developing contemporary ecclesiologies - Schoeman, W. J. (University of the Free State theological explorations, 2020)
Ecclesiology is the study of the church and has two focal points; the one is the historical and doctrinal perspective on the church, and the other is the church as situated in a local context in the sense of the local practices of actual congregations. The ecclesiology or, more correctly, the ecclesiologies of this volume mainly focuses on the second aspect, i.e., understanding the local congregation or parish as a community of believers. A congregation may firstly be described by posing a theological question: What is the local missional church or congregation all about? This question may be answered from different perspectives, but it remains essential to answer it from a theological perspective. The first five chapters in this book focus mainly on a theological understanding of the congregation. This is done from different disciplines within the study field of theology. Congregations are, secondly, social realities and should be described and analysed through an analytical or empirical lens, or, to answer the question attached to the first empirical-descriptive task of practical theology, "What is going on?". The remaining chapters use a quantitative and qualitative lens and give an empirical analysis of the congregation. The intention is to critically reflect on the church and congregations' ecclesiology from a theological and analytical perspective with an emphasis on the South African context. It wants to map markers for the development of contemporary ecclesiologies, and the different chapters are meant as mirrors to look in and reflect on the theological and contextual relevance of denominations and congregations in South Africa